(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Indonesia has a wealth of natural resources, especially in the fishing sector. The waters of Lamongan are one of the areas that has the potential of swanggi fishing that dominates the fishing sector by catching cantrang fish. The research is aimed at providing information to the Brondong National Fishing Port (PPN) and fishermen around the area about the impact of rainfall and wind speed on the catch of swanggi fish. The results of linear regression method analysis using T test, F test and determination test. The result of lineary regression test T test showed that the regression value of the rainfall variable to catch of fish is the value of sig.<0,05 while the variable of wind speed to Catch of Fish is the number of sig.>0,05. The determination test result of R2 is 0.445, which means that the variable rainfall and wind speed influenced 44.5% on the catch of the swanggi fish and the rest was affected by other factors.